Students’ perception toward English subject and their learning outcome - Hafrizal Hafrizal; Usman Kasim; Iskandar Abdul Samad (English Education Journal, 2021)
This research aims to find out students' perception of the English subject and provides an overview of the students learning outcome at SMA Negeri 1 Jangka Buya, Pidie Jaya. The instruments used in this research are questionnaires, interview guides, and documentation. Students' perceptions are classified into three categories: education, economy, and social interaction, and one group of negative question models support the other three. The student's perception of English is dominant in education. Generally, the students of SMAN 1 Jangka Buya come from dayah (Islamic school). They believe that mastering English can help them promote Islamic teachings more effectively. The negative question is the second dominant result; most students admit that language is a medium to build up connection and communication verbally or through written text. Meanwhile, in the economy category, students believe that we can increase income with English language skills. It is also shown that students who have good grades in English also have a high perception of certain categories. In comparison, students who have low perception get low learning outcomes on the English subject. So that, the students' perception and background must be hardly noticed by the teacher in planning a good teaching and learning process.